Hegemoni orang tua pada pemilihan jurusan pariwisata bagi siswa di smk pgri 3 denpasar - Libhi, Putu Suratin Surya; Dhana, I Nyoman; Winaja, I Wayan (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 2 (2018): Vol.2,No.2,2018DO - 10.24843/JKH.2018.v02.i02.p08, 2018)
This article examines the current state of tourism education that is influenced by the condition of the tourism industry in Bali. The development of tourism has implications on the various things in the life of a cultured society, not least the state of the family structure in choosing education for their children which is considered for parents. This article relies on a more specific point of examining how parents are acting so hegemonic to their children that it leads the child to choose a course of tourism in a vocational high school. Qualitative approach used in describing and understanding a problem supported by quantitative data. The data were extracted through the process of observation, documentation and interview. The results show if parents have a big share of the decision in choosing education for their children, especially leading to tourism education. this is influenced by the current state of tourism development. Parents of students have the ideology of capitalism in sending their children to education tourism as an investment by way of investing in their children so that later can be picked by parents when the child completed education and get a decent job in accordance with the plans of parents. But the important thing is, the child has other interests and talents, not on tourism education such as mechanical and musical techniques so that coercive coercion called hegemony exists in this phenomenon. consequently that happens is when this child through the process of teaching and learning in the classroom occurs not seriusan or lack of interest in learning to students so that students perform actions that are not desired by parents and the school such as lazy to go to school, lazy to make tasks given teachers and things - other things are based on the unfavorable.   Keywords:     Hegemony, Tourism Department, Tourism Development,                      Tourism industry